ECHINOCOCCOSIS OF THE LIVER COMPLICATED BY A BREAKTHROUGH INTO THE BILIARY TRACT AND THE DEVELOPMENT OF MECHANICAL JAUNDICE: DIAGNOSIS AND TREATMENT (LITERATURE REVIEW) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Hepatic echinococcosis is a serious medical issue, especially in endemic regions. Complications of the disease, such as cyst rupture into the bile ducts leading to the development of mechanical jaundice, occur in 10-30% of patients and significantly worsen the clinical course, resulting in cholangitis, liver abscesses, and liver failure. Diagnosing these conditions requires the use of high-precision imaging techniques such as ultrasound, MRCP, and ERCP. The rupture of an echinococcal cyst into the bile ducts necessitates a multidisciplinary approach, including endoscopic removal of parasitic elements and surgical intervention, followed by bile duct drainage. Modern techniques, such as minimally invasive endoscopic procedures, reduce the risk of postoperative complications and improve treatment outcomes.